2015
DOI: 10.3233/jad-141704
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Channel Kv1.3 Is Highly Expressed by Microglia in Human Alzheimer's Disease

Abstract: Recent genetic studies suggest a central role for innate immunity in Alzheimer’s disease (AD) pathogenesis, wherein microglia orchestrate neuroinflammation. Kv1.3, a voltage-gated potassium channel of therapeutic relevance in autoimmunity, is upregulated by activated microglia and mediates amyloid-mediated microglial priming and reactive oxygen species production in vitro. We hypothesized that Kv1.3 channel expression is increased in human AD brain tissue. In a blinded postmortem immunohistochemical semi-quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 45 publications
2
100
0
Order By: Relevance
“…10). Because CFZ selectively inhibits Kv1.3 function (Ren et al, 2008), and Kv1.3 channels are considered principal regulators of microglial cell reactivity (Rangaraju et al, 2015), we focused on microglial labeling differences. In normal untreated callosal cultures, Kv1.3 expression was evident for each microglial morphology present, even in cells with lower IBA1 signal (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…10). Because CFZ selectively inhibits Kv1.3 function (Ren et al, 2008), and Kv1.3 channels are considered principal regulators of microglial cell reactivity (Rangaraju et al, 2015), we focused on microglial labeling differences. In normal untreated callosal cultures, Kv1.3 expression was evident for each microglial morphology present, even in cells with lower IBA1 signal (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our observations that postinjury axonal function can be altered by Kv1.3 manipulation, and that white matter microglia potentially mediate this effect through Kv1.3 regulation of inflammatory molecules, are supported by Kv1.3 studies using models of neurodegeneration and epilepsy. Postmortem analysis of Alzheimer’s disease patients revealed significantly higher levels of Kv1.3 channels co-localized with microglial cells, but not with astrocytes (Rangaraju et al, 2015). Kv1.3 was shown to be highly expressed on inflammatory leukocyte infiltrates in brains from multiple sclerosis patients, and Kv1.3 was elevated in both gray and white matter (Rus et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Kir channels are also expressed, but the noteworthy finding is the lack of K V 1.3 expression and presence of K Ca 1.1 instead. What is particularly surprising about the missing functional K V 1.3 expression, is that several immunohistochemistry studies have previously shown strong K V 1.3 specific staining on activated microglia in human ischemic infarcts, 22 microglia surrounding amyloid-plaques in Alzheimer disease, 41 as well as on cells with a glia morphology in active multiple sclerosis lesions. 42 Combined with our finding that cultured prenatal human microglia clearly express K V 1.3, and that microglia exhibit such a pronounced and stimulidependent expression plasticity, a reasonable assumption is that the "adult epilepsy microglia phenotype" carries a unique set of K C channels dictated by their specific aging and/or epilepsy/medication history.…”
Section: Future Directions Toward An Integrated View Of Kmentioning
confidence: 99%
“…DAB-peroxidase immunohistochemistry was performed using antibodies directed against alpha synuclein (phospho S129) (1:500; Abcam, Melbourne, Australia) [20] and p62 (1:100; BD Biosciences, CA, USA) for macrophagy [21]. The doublelabelled fluorescent immunohistochemistry was performed using antibodies directed against Iba1 (1:100; Abcam, Melbourne, Australia) for microglia [22] and Human Leukocyte Antigen -antigen D Related (HLA-DR, 1:200, Dako Corporation, Carpinteria, CA, USA) for activated microglia [23]. The experimental procedures have been described previously [3,19].…”
Section: Immunohistochemistrymentioning
confidence: 99%